2018
DOI: 10.1088/1361-6528/aaa449
|View full text |Cite
|
Sign up to set email alerts
|

Improved field emission properties ofα-Fe2O3nanoflakes with current aging treatment and morphology optimization

Abstract: a-Fe2O3 nanomaterials were synthesized by thermal oxidation of pure iron foil, and the effects of current aging treatment and morphology on their field emission properties were systematically investigated. Current aging treatment was found to be an efficient method to improve the field emission properties of a-Fe2O3 nanoflakes. Emission current density was largely enhanced from 0.05 to 5.70 mA/cm2 under an applied electrical field of 7.8 MV/m, and their threshold field decreased from larger than 11.0 to 6.6 MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Usually, the iron oxide surface requires prolonged treatment at elevated temperatures to obtain the hematite phase and the typical morphology suitable for eldeffect electron emission. 10,25,30,43,44 From Table 4, PATO-processed lms revealed that the method of processing strongly affects the eld emission performance; the PATO-processed lms with unique morphologies were better than the conventionally processed lms. The difference in eld emission performance in the PATO-processed M-Fe and N-Fe lms was due to the surfacestabilized phase and morphology obtained in a given oxygen environment.…”
Section: Field Emission (Fe) Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Usually, the iron oxide surface requires prolonged treatment at elevated temperatures to obtain the hematite phase and the typical morphology suitable for eldeffect electron emission. 10,25,30,43,44 From Table 4, PATO-processed lms revealed that the method of processing strongly affects the eld emission performance; the PATO-processed lms with unique morphologies were better than the conventionally processed lms. The difference in eld emission performance in the PATO-processed M-Fe and N-Fe lms was due to the surfacestabilized phase and morphology obtained in a given oxygen environment.…”
Section: Field Emission (Fe) Analysismentioning
confidence: 99%
“…To improve the performance of eld emitters, nanoscale materials have been used. 10,[25][26][27][28][29][30][31] Nanostructured materials possess high aspect ratios, as well as high surface activity, and are, therefore, suitable for applications like eldeffect electron emission, gas sensors, 32 catalysts, 33,34 magnetic storage devices, 35 anode material for lithium-ion batteries, 36 thermoelectric power generators, 37 nuclear radiation sensors, 38 etc. Looking at the eld emission properties of nanostructures grown on surfaces, researchers have reported that carbon nanotubes are excellent eld emitters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations